Effect of maghemization on the magnetic properties of nonstoichiometric pseudo-single-domain magnetite particles - Almeida,TP; Muxworthy,AR; Kasama,T; Williams,W; Damsgaard,C; Frandsen,C; Pennycook,TJ; Dunin-Borkowski,RE (Geochemistry Geophysics Geosystems, 2015)
The effect of maghemization on the magnetic properties of magnetite (Fe3O4) grains in the pseudo-single-domain (PSD) size range is investigated as a function of annealing temperature. X-ray diffraction and transmission electron microscopy confirms the precursor grains as Fe3O4 ranging from ~ 150 nm to ~ 250 nm in diameter, whilst Mössbauer spectrometry suggests the grains are initially near-stoichiometric. The Fe3O4 grains are heated to increasing reaction temperatures of 120 – 220 ºC to investigate their oxidation to maghemite (γ-Fe2O3). High-angle annular dark field imaging and localized electron energy loss spectroscopy reveals slightly oxidized Fe3O4 grains, heated to 140 ºC, exhibit higher oxygen content at the surface. Off-axis electron holography allows for construction of magnetic induction maps of individual Fe3O4 and γ-Fe2O3 grains, revealing their PSD (vortex) nature, which is supported by magnetic hysteresis measurements, including first order reversal curve analysis. The coercivity of the grains is shown to increase with reaction temperature up to 180 ºC, but subsequently decreases after heating above 200 ºC; this magnetic behavior is attributed to the growth of a γ-Fe2O3 shell with magnetic properties distinct from the Fe3O4 core. It is suggested there is exchange coupling between these separate components that results in a vortex state with reduced vorticity. Once fully oxidized to γ-Fe2O3, the domain states revert back to vortices with slightly reduced coercivity. It is argued that due to a core/shell coupling mechanism during maghemization, the directional magnetic information will still be correct, however, the intensity information will not be retained.